Histopathological changes in gill of Nile tilapia (Oreochromis niloticus) after palm oil mill effluent exposure. (December 2018) - Muliari,; Akmal, Y; Zulfahmi, I; Juanda, R; Karja, N W K; Nisa, C
Abstract: Histopathological studies have been widely used as a tool for detection and assessment the negative effects of pollutants on fish. This present study aimed to determine and analyze the histopathological changes of gills in Nile tilapia after exposed to Palm Oil Mill Effluent (POME). Toxicological/chronic concentration in each treatment was based on LC50 -96 hours value of POME on Nile tilapia obtained from the previous study which was 15.65 mg/L. The fish were devided into five treatment with 10 fish were used in each treatment. Treatment were design as follows: Treatment control (0% POME: 0 mg/L), Treatment A (10% of LC50 -96 hour value: 1.565 mg/L), Treatment B (15% of LC50 -96 hour value: 2.347 mg/L), and Treatment C (20% of LC50 -96 hours: 3.130 mg/L). The exposure period lasts for 45 days. The result shows that POME exposure has a negative impact caused histopathological changes in the gill of Nile tilapia. The gill lesion due to POME exposure observed in this study were erythrocyte infiltration, hyperplasia, epithelial lifting and lamellar fusion.